Exploring Perceus for OCaml - Pinto, Elton; Leijen, Daan (2023)
The Perceus algorithm is a precise and garbage-free reference counting scheme which shows good performance in practice. However, the algorithm has only been compared against garbage-collection across different systems and languages. There is no direct comparison between Perceus and a garbage collector within the same system. In this work, we take an initial step towards this goal. We have implemented a prototype of Perceus for OCaml 4.14.0 (which subsumes the standard garbage collector). Now we can directly compare the performance of programs compiled with the exact same compiler, where we only switch the backend: either using the standard generational collector, or using Perceus compilation with a reference counted runtime system. The initial performance results look quite promising, motivating futher exploration.
Presented at the "Higher order, Typed, Strict: ML Family Workshop 2023" co-located with ICFP'23.